Students’ attitude towards different modalities of teaching in the medical curriculum of the faculty of physiology, SKIMS Medical College, Bemina - Ahad, Farhana; Shafi, Mudasir; Hameed, Reqaya (International Journal Of Community Medicine And Public Health, 2023)
Background: The way that students learn and the caliber of their learning results are both influenced by their judgments about their learning modes. The clinical portion of undergraduate medical courses is conducted in a setting intended more for clinical service than for instruction. When these two activities fight for resources, tension results. A projected rise in the number of medical students prompted us to evaluate the learning environment in order to make future plans. Objective was to evaluate students’ attitude towards different modalities of teaching in the medical curriculum of the faculty of physiology, SKIMS medical college, Bemina. Methods: 200 SKIMS medical college students between the ages of 19 and 25 participated in a questionnaire-based study starting in October 2022. The phrasing of the question is repeated below. Each teaching method- lectures, handouts, textbooks, media sites (video-recorded lectures), simulation, PBL (problem-based learning), TBL (team-based learning), and ICM (introduction to clinical medicine, physical examination) practicals- was the subject of five questions. Answers were on a 5-step Likert scale. Results: It was a descriptive type of research in nature. The data has been collected with the help of a structured questionnaire based on the Likert scale. Conclusions: The study’s overall conclusions demonstrated that there had been significant changes in attitudes regarding professional development, team experiences, and peer evaluation.